Arterial Catheters for Early Detection and Treatment of Hypotension During Major Noncardiac Surgery: A Randomized Trial. (November 2020) - Naylor, Amanda J.; Sessler, Daniel I.; Maheshwari, Kamal; Khanna, Ashish K.; Yang, Dongsheng; Mascha, Edward J.; Suleiman, Iman; Reville, Eric M.; Cote, Devan; Hutcherson, Matthew T.; Nguyen, Bianka M.; Elsharkawy, Hesham; et al.
Abstract : BACKGROUND: Continuous blood pressure monitoring may facilitate early detection and prompt treatment of hypotension. We tested the hypothesis that area under the curve (AUC) mean arterial pressure (MAP) <65 mm Hg is reduced by continuous invasive arterial pressure monitoring. METHODS: Adults having noncardiac surgery were randomly assigned to continuous invasive arterial pressure or intermittent oscillometric blood pressure monitoring. Arterial catheter pressures were recorded at 1-minute intervals; oscillometric pressures were typically recorded at 5-minute intervals. We estimated the arterial catheter effect on AUC-MAP <65 mm Hg using a multivariable proportional odds model adjusting for imbalanced baseline variables and duration of surgery. Pressures <65 mm Hg were categorized as 0, 1–17, 18–91, and >91 mm Hg × minutes of AUC-MAP <65 mm Hg (ie, no hypotension and 3 equally sized groups of increasing hypotension). RESULTS: One hundred fifty-two patients were randomly assigned to arterial catheter use and 154 to oscillometric monitoring. For various clinical reasons, 143 patients received an arterial catheter, while 163 were monitored oscillometrically. There were a median [Q1, Q3] of 246 [187, 308] pressure measurements in patients with arterial catheters versus 55 (46, 75) measurements in patients monitored oscillometrically. In the primary intent-to-treat analysis, catheter-based monitoring increased detection of AUC-MAP <65 mm Hg, with an estimated proportional odds ratio (ie, odds of being in a worse hypotension category) of 1.78 (95% confidence interval [CI], 1.18–2.70; P = .006). The result was robust over an as-treated analysis and for sensitivity analyses with thresholds of 60 and 70 mm Hg. CONCLUSIONS: Intraoperative blood pressure monitoring with arterial catheters detected nearly twice as much hypotension as oscillometric measurements.